Promoting Reading Comprehension in the Secondary English Classroom (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
Reading comprehension, defined as the ability to process text and understand its meaning, has been identified as a problem among middle and high school students. Despite decades of research on reading comprehension, American adolescents' reading scores show stagnant growth. Reading comprehension is a vital part of instruction, specifically in secondary English classrooms as the texts students are asked to read become increasingly complex. According to researchers, reading strategies can play an important role in developing student comprehension. However, these strategies are often not taught because many teachers lack the foundation for teaching them. This paper will discuss frameworks, systems, and effective reading strategies that engage struggling readers in comprehending text.
Keywords: Reading; Reading strategies; Comprehension; SQ3R; Reciprocal Teaching